Light-Inducible and Clock-Controlled Expression of MAP Kinase Phosphatase 1 in Mouse Central Pacemaker Neurons - Doi, Masao; Cho, Sehyung; Yujnovsky, Irene; Hirayama, Jun; Cermakian, Nicolas; Cato, Andrew C.B; Sassone-Corsi, Paolo (Journal of biological rhythms, 2007)
MAP kinase phosphatase 1 (MKP1) is a negative regulator for the mitogen-activated protein kinase (MAPK)--mediated signal transduction, a key pathway that leads to the regulated expression of circadian clock genes. Here the authors analyzed mkp1 expression by in situ hybridization and found that mkp1 is a light-inducible and clock-controlled gene expressed in the central pacemaker neurons of the hypothalamic SCN. Interestingly, mkp1 presents a marked similarity to the clock core gene per1 in terms of the gene expression profiles as well as the gene promoter organization. Both mkp1 and per1 are subject to bimodal regulation in the SCN: the external light-dependent acute up-regulation and the functional clock-dependent circadian oscillation. Consistent with this, the authors show that mkp1 gene has a per1-like promoter that contains 2 functionally distinct elements: cAMP-responsive element (CRE) and E-box. CRE sites present in the mkp1 promoter constitute the functional binding sites for the CRE binding protein (CREB), which serves as an important regulator that mediates the light-induced signaling cascades in the SCN neurons. Furthermore, the authors show that the E-box present in the mkp1 promoter is necessary and sufficient for transcriptional control exerted by circadian clock core regulators that include a positive complex CLOCK/BMAL1 and a negative factor CRY1. The authors' studies on mkp1 have identified for the first time a gene encoding a phosphatase that functions in light-dependent and time-of-day-dependent manners in the mammalian central clock structure SCN.